The recent convergence on the NW Borneo Wedge-a crustal-scale gravity gliding evidenced from GPS - Sapin, Francois (2020)
The existence of an active compression on the frontal fold-and-thrust belt (FTB) of the NW Borneo Wedge is a long debate. Because of the absence of seismicity, the frontal FTB is traditionally considered as inactive and generally attributed to the thin-skin gravity-driven Baram Basin. However, there are some signs of convergence and compression (GPS velocities and horizontal stress field measured from borehole analysis) do exist between the NWBorneo area and Sunda Plate (Dangerous-Grounds). Revisited GPS data, combined with a rigorous structural study of theNWBorneoWedge suggest that the recent compression recorded on the frontal FTB is the result of a crustal-scale gravity-driven mechanism, the orogenic collapse of the NW Borneo in the Sabah-northern Sarawak area since 1.9 Myr. These results provide a new understanding of the recent behaviour of the NW Borneo Wedge which can be included in a continuum of the wedge history.